On the benefits of the tryptophan metabolite 3-hydroxyanthranilic acid in Caenorhabditis elegans and mouse aging - Hope Dang; Raul Castro-Portuguez; Luis Espejo; Grant Backer; Samuel Freitas; Erica Spence; Jeremy Meyers; Karissa Shuck; Emily A. Gardea; Leah M. Chang; Jonah Balsa; Niall Thorns; et al. (Nature Communications, 2023)
Abstract Tryptophan metabolism through the kynurenine pathway influences molecular processes critical to healthy aging including immune signaling, redox homeostasis, and energy production. Aberrant kynurenine metabolism occurs during normal aging and is implicated in many age-associated pathologies including chronic inflammation, atherosclerosis, neurodegeneration, and cancer. We and others previously identified three kynurenine pathway genes—tdo-2, kynu-1, and acsd-1—for which decreasing expression extends lifespan in invertebrates. Here we report that knockdown of haao-1, a fourth gene encoding the enzyme 3-hydroxyanthranilic acid (3HAA) dioxygenase (HAAO), extends lifespan by ~30% and delays age-associated health decline in Caenorhabditis elegans. Lifespan extension is mediated by increased physiological levels of the HAAO substrate 3HAA. 3HAA increases oxidative stress resistance and activates the Nrf2/SKN-1 oxidative stress response. In pilot studies, female Haao knockout mice or aging wild type male mice fed 3HAA supplemented diet were also long-lived. HAAO and 3HAA represent potential therapeutic targets for aging and age-associated disease.